The wandering Jew in America - Rebhun, Uzi (Jewish identities in post modern society., 2011)
Uzi Rebhun provides the reader with a thorough description and analysis of the multifaceted nature of Jewish internal migration in the United States. Using data from the 1990 and 2000 NJPS, and through up-to-date approaches in the social sciences, he traces changes in the levels, directions, and types of Jewish migration, evaluating the changing social and economic characteristics of the migrants. Finally, Rebhun tests the relationships between migration and Jewish behavior in both the private and public spheres, his findings contributing to the theoretical literature on internal migration and to a better understanding of American ethnicity. The Wandering Jew in America is an excellent resource for students of migration, ethnicity, and sociology of religion, as well as those interested in Jewish life in America.